Aplatophis zorro, a new species of eastern Pacific snake-eel, with comments on New World ophichthid distributions (Anguilliformes: Ophichthidae) - McCosker, John E. (2001)
Aplatophis zorro n. sp., the first known eastern Pacific species of this New World genus, is described from a shallow water trawl-caught specimen from the Golfo de San Miguel, Pacific Panama. It is similar to its only known congener, A. chauliodus from the tropical western Atlantic, but differs in its vertebral number, dentition, coloration, and other characters. Comments concerning the distribution of New World ophichthids are provided.